All-solid-waste-system lightweight baking-free brick based on carbon dioxide foaming technology and preparation method of all-solid-waste-system lightweight baking-free brick
By adopting carbon dioxide foaming technology and a full solid waste system in the production of burn-free bricks, the bricks' self-weight and energy consumption problems are solved, and the effects of lightweight and carbon sequestration and emission reduction are achieved.
Patent Information
- Application Number
- CN202510153034.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-15
AI Technical Summary
In the existing production of fire-free bricks, there are problems such as bricks being self-weighted, requiring pre-dehydration and mechanical pressing, and the waste mud and bulk solid waste cannot be effectively utilized.
The lightweight, burn-free brick is adopted for the all-solid waste system based on carbon dioxide foaming technology. The waste mud, desulfurization gypsum, alkali trigger, slag and carbon dioxide foam are mixed in a specific proportion, and aged in a dry and ventilated place, it is naturally air-dried and reasonably maintained for solidification.
The significant lightweight of the bricks is achieved, the self-weight is reduced, the need for pre-dehydration and mechanical press forming is avoided, and the carbon dioxide is solidified into the bricks through carbon dioxide foaming technology, increasing carbon sinks.
Smart Images

Figure CN119822712A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon capture and resource utilization, and more specifically to a full solid waste system lightweight unfired brick based on carbon dioxide foaming technology and a preparation method thereof. Background Art
[0002] When the project is completed or fails to meet the use requirements, the engineering mud is usually disposed of. However, due to the characteristics of relatively high viscosity, small particles and poor gradation of engineering mud, it is difficult to separate by natural sedimentation. At the same time, the large amount of engineering mud accumulation will not only pollute the surrounding environment, but also pose potential risks to the later development of the site. Even if a dedicated waste mud landfill is built, it will occupy a large amount of space resources. Therefore, how to deal with waste mud has become an urgent problem that needs to be solved.
[0003] At the same time, industrial activities will generate a large amount of bulk solid waste, such as blast furnace slag, industrial by-product desulfurized gypsum, etc. Since slag itself has potential hydraulic hardness, it will produce good activity after chemical stimulation such as alkali stimulation and sulfate stimulation. The sulfate rich in industrial by-product gypsum has a good stimulation effect in an alkaline environment. Adding alkaline substances and industrial by-product gypsum to slag can achieve two-way stimulation of alkali stimulation and sulfate stimulation, thereby improving the curing effect of the curing agent.
[0004] At present, there are many kinds of masonry bricks used in construction production. Among them, compared with traditional red bricks made of clay as raw material, unburned bricks, as a new type of masonry bricks manufactured without high-temperature calcination, use waste as the main raw material, which has the advantages of saving energy and protecting the environment. Therefore, the unburned bricks prepared based on waste mud and bulk solid waste can, on the one hand, turn waste into treasure and treat waste mud with high added value; on the other hand, it can realize the comprehensive utilization of bulk solid waste and reduce land resource consumption and environmental pollution. However, the unburned bricks prepared in this way still have problems such as heavy weight and the need for additional energy-added steps such as pre-dehydration and mechanical pressing.
[0005] As an emerging technology, carbon dioxide foaming technology brings hope for preparing lightweight unfired bricks while capturing carbon dioxide to increase carbon sinks. Therefore, in response to the government's dual carbon strategy call and the lightweight development of unfired bricks, it is urgent to develop a full solid waste system lightweight unfired brick based on carbon dioxide foaming technology and its preparation method in this field. Summary of the invention
[0006] The purpose of the present invention is to provide a fully solid waste system lightweight unburned brick based on carbon dioxide foaming technology and a preparation method thereof, so as to solve the problems faced by existing unburned brick production, such as heavy weight of bricks, need for pre-dehydration, and need for mechanical pressing and forming. At the same time, it contributes to capturing carbon dioxide, fixing carbon emissions, and increasing carbon sinks.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A full solid waste system lightweight unburned brick based on carbon dioxide foaming technology, comprising the following components in parts by weight:
[0009] 65-70 parts of waste mud, 14-18 parts of carbon dioxide foam, 3-5 parts of desulfurized gypsum, 3-5 parts of alkali activator, and 5-7 parts of slag.
[0010] Preferably, the carbon dioxide foam is obtained by whipping a foaming solution at a rate of 600 r / min in a closed carbon dioxide environment.
[0011] Preferably, the foaming solution is obtained by mixing 4.5 g / L of dodecylamine polyoxyethylene ether and 2 g / L of hydroxypropyl methylcellulose.
[0012] Preferably, the pore size of the carbon dioxide foam is 0.8 to 1 mm, more preferably 0.8 to 0.85 mm, and more preferably 0.8 mm.
[0013] Preferably, the water content of the waste sludge is 100-120%, more preferably 110%-120%, and even more preferably 115%-120%.
[0014] Preferably, the particle size of the desulfurized gypsum is less than 0.08 mm, more preferably ≤0.07 mm, and even more preferably ≤0.05 mm.
[0015] Preferably, the alkaline activator is MgO, and the particle size of the alkaline activator is less than 0.08 mm, more preferably ≤0.07 mm, and even more preferably ≤0.05 mm.
[0016] Preferably, the slag is S95 grade slag powder, and the particle size of the slag is 46 to 100 μm, more preferably 50 to 95 μm, and even more preferably 80 to 90 μm.
[0017] Another object of the present invention is to provide a method for preparing the above-mentioned all-solid waste system lightweight unburned brick based on carbon dioxide foaming technology, comprising the following steps:
[0018] (1) Pass the waste mud through a 2mm round hole sieve to remove waste plastics, gravel and other debris from the waste mud for later use;
[0019] (2) drying the desulfurized gypsum, alkali activator and slag respectively, then grinding and sieving to obtain original powder;
[0020] (3) Weighing the waste mud, desulfurized gypsum, alkali activator and slag in proportion;
[0021] (4) pouring the components weighed in step (3) into a blender and mixing at a stirring rate of 1000 r / min for 30 min to obtain a mixture I;
[0022] (5) mixing 4.5 g / L of dodecylamine polyoxyethylene ether and 2 g / L of hydroxypropyl methylcellulose to obtain a foaming solution, whipping the solution at a rate of 600 r / min in a closed carbon dioxide environment to obtain carbon dioxide foam, and taking a proportional amount of the carbon dioxide foam;
[0023] (6) adding carbon dioxide foam to mixture I and mixing at a stirring rate of 60 r / min for 7 min to obtain mixture II;
[0024] (7) Place the mixture II in a dry and ventilated place for aging for 6-10 hours, turning it 4-5 times during the aging process;
[0025] (8) Pour the aged mixture II into the brick mold, smooth the surface, and solidify it after natural drying and proper maintenance;
[0026] (9) demoulding and sampling, taking out the solidified brick along the direction of the mold groove to obtain the unfired brick sample;
[0027] (10) The unfired brick sample is placed at 20±2° C. and cured at a humidity of 90% for 28 days to obtain a final product, a lightweight unfired brick.
[0028] Preferably, the carbonization reaction process occurring during the mixing of the carbon dioxide foam and the mixed slurry is as follows:
[0029] MgO+H 2 O→Mg(OH) 2
[0030] Mg(OH) 2 +CO 2 +2H 2 O→MgCO 3 ·3H 2 O
[0031] Mg(OH) 2 +CO 2 →Mg 5 (CO 3 )4(OH) 2 ·4H 2 O
[0032] 5Mg(OH) 2 +4CO 2 +H 2 O→(Mg) 5 (CO 3 )4 (OH) 2 ·5H 2 O
[0033] Ca(OH) 2 +CO 2 →CaCO 3
[0034] 3CaO·2SiO 2 ·3H 2 O+CO 2 →CaCO 3 +2CaO·2SiO 2 ·3H 2 O
[0035] 3CaO·2SiO 2 ·3H 2 O+2CO 2 →2CaCO 3 +CaO·2SiO 2 ·3H 2 O
[0036] 3CaO·2SiO 2 ·3H 2 O+3CO 2 →3CaCO 3 +2SiO 2 ·3H 2 O.
[0037] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The present invention digests the waste mud generated by various projects to a great extent, solves the problem that the waste mud yard occupies a large amount of space resources and pollutes the surrounding ecological environment. At the same time, the waste mud used does not need to be dehydrated in advance, reducing the energy consumption and cost generated by the dehydration process.
[0039] (2) The present invention uses desulfurized gypsum and slag, which are large-scale solid wastes generated in industrial activities, to solidify the waste mud, such as Figure 3 As shown, compared with transporting solid waste to landfill for disposal, using traditional cement-based materials for solidification, and using alkali-activated slag for solidification, it has the advantage of lower carbon emissions, conforms to the economic concept of low-carbon, green and environmentally friendly development, and helps to promote the comprehensive utilization of bulk solid waste and realize green, efficient, high-quality and high-value development and utilization.
[0040] (3) The present invention adds carbon dioxide foaming technology to the traditional unburned brick preparation technology, such as Figure 4As shown, under the condition that other conditions remain the same, only the content of carbon dioxide foam is changed. Under the appropriate ratio, the prepared carbon dioxide lightweight unfired bricks can not only achieve the compressive strength of MU7.5, but also significantly reduce the weight of the bricks without the need for mechanical pressing and forming, solving the problem of heavy bricks and the need for mechanical pressing and forming in the current construction industry.
[0041] (4) The lightweight unfired bricks prepared by the present invention using carbon dioxide foaming technology can effectively solidify carbon dioxide in the unfired bricks, have the ability to increase carbon sinks, and have high practical application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0043] Figure 1 A flow chart was prepared for the present invention.
[0044] Figure 2 It is an operation flow chart of the present invention.
[0045] Figure 3 This is a comparison chart of carbon emissions generated by different waste mud treatment methods.
[0046] Figure 4 This is a comparison chart of the dry density and strength of unfired bricks at different carbon dioxide foam dosages. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The embodiment of the present invention discloses a full solid waste system lightweight unburned brick based on carbon dioxide foaming technology, comprising the following components in parts by weight:
[0049] 65-70 parts of waste mud, 14-18 parts of carbon dioxide foam, 3-5 parts of desulfurized gypsum, 3-5 parts of alkali activator, and 5-7 parts of slag.
[0050] In the present invention, the waste mud is selected from waste mud from urban underground space construction, dredging engineering, island and reef engineering, shield excavation and other projects.
[0051] The screening of carbon dioxide foam components is shown in the following table:
[0052] Table 1 Comparison of carbon dioxide foaming solution properties
[0053]
[0054] Note: 1. The stability of water-based foam is measured by the half-dissipation time of the foam, that is, the time consumed when the foam volume dissipates to half of its original volume. The half-dissipation time of the foam is recorded as the half-life of the foam. In this test, the generated carbon dioxide foam is taken in the same volume (6000cm 3 ) into the cup and start timing until the foam dissipates to 3000cm 3 , get the half-life of each group of foams;
[0055] 2. The foaming ability of water-based foam is measured by the foaming multiple, and the ratio of the foam volume to the foaming solution volume is recorded as the foaming multiple.
[0056] Based on the above preliminary tests, the foaming solution was obtained by mixing 4.5 g / L of dodecylamine polyoxyethylene ether and 2 g / L of hydroxypropyl methylcellulose.
[0057] In the preparation method of the present invention, water mainly plays the role of dispersing the original waste mud soil, making it easier to stir the original waste mud soil with desulfurized gypsum, alkali activator and slag, and the contact between the two is more sufficient. However, too much water will make the fluidity of the mixture too high, which will eventually lead to low viscosity of the mixture, making it difficult to form lightweight unburned bricks. At the same time, too high fluidity will increase the curing time, resulting in an increase in the time cost of recycling the waste mud. Therefore, as a preferred embodiment, the water content of the waste mud is 120%; at the same time, in order to improve the mixing efficiency of the waste mud and desulfurized gypsum, magnesium oxide and slag, and prevent the debris in the waste mud from interfering with the mixing process, the waste mud is first passed through a 2mm round hole sieve to remove waste plastics, gravel and other debris in the waste mud soil.
[0058] In order to improve the mixing efficiency of waste mud and desulfurized gypsum, magnesium oxide and slag, the desulfurized gypsum, alkali activator and slag are first dried separately, then ground and passed through a 200-mesh sieve to obtain the original powder. Therefore, as a preferred method, the particle size of the desulfurized gypsum is 0.08 mm; the alkali activator is magnesium oxide, and the particle size of the alkali activator is 0.08 mm; the slag is S95 grade slag powder, and the particle size of the slag is 46-100 μm.
[0059] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0060] The parts described in the following examples are all parts by mass.
[0061] Example 1
[0062] The present embodiment provides a kind of unburned brick made of waste mud, which includes 69 parts of waste mud with a water content of 110% produced by dredging projects, 14 parts of carbon dioxide foam with a pore size of 0.8 mm, 3.5 parts of desulfurized gypsum with a particle size of 0.08 mm, 3.5 parts of magnesium oxide with a particle size of 0.08 mm, and 6 parts of S95 grade slag powder with a particle size of 95 μm.
[0063] The preparation process is as follows:
[0064] (1) Sampling the waste mud generated by the dredging project with a water content of 110%: sieving the waste mud with a sieve aperture of 10 mesh to remove waste plastics, gravel and other debris contained in the waste mud;
[0065] (2) pre-treating the desulfurized gypsum, magnesium oxide and S95 grade slag powder respectively, drying the desulfurized gypsum, magnesium oxide and S95 grade slag powder in an environment of 24° C. for 6 hours, then grinding them, and finally passing through a sieve with an aperture of 200 meshes, and then mixing the three to obtain a mixed powder;
[0066] (3) placing the mixed powder and the sieved waste mud together in a mixer, and performing a mixing operation at a speed of 1200 r / min for 40 minutes to obtain a mixed material;
[0067] (4) mixing 4.5 g / L of dodecylamine polyoxyethylene ether with 2 g / L of hydroxypropyl methylcellulose to obtain a foaming solution, and whipping the solution at a rate of 600 r / min in a closed carbon dioxide environment to obtain carbon dioxide foam;
[0068] (5) taking carbon dioxide foam according to a certain ratio and mixing it into the mixture, continuing to mix at a speed of 60 r / min for 6 minutes, and then placing it in a dry and ventilated place for aging for 6 hours, turning it over 4 times during the aging period;
[0069] (6) Pour the mixture obtained after aging treatment into a brick mold (the brick mold is a 95 standard brick mold, and its size (length × width × height) is 240 × 115 × 53 mm), and solidify it at 20°C for 40 hours. Then, the solidified brick is taken out along the direction of the brick mold groove, and finally placed in an environment with a temperature of 20°C and a humidity of 95% for 28 days of curing, thereby obtaining a lightweight unfired brick.
[0070] The performance of the unburned brick obtained in this embodiment was tested. Referring to the specification "Standard for Geotechnical Test Methods" (GB / T50123-2019), it was determined that the compressive strength of the unburned brick was 10.2 MPa, the water absorption rate was 15%, and the softening coefficient was 0.8.
[0071] The method for determining the dry density and carbon fixation rate of bricks in this embodiment and the subsequent examples is as follows:
[0072] 1. Dry density test
[0073] After a group of unfired bricks were subjected to unconfined compressive strength tests, some of the broken pieces were dried and weighed to obtain the dry weight m 0 Heat the solid paraffin in an electric furnace until it melts, wrap the dried sample with the melted paraffin and weigh it to get the weight of the sample and paraffin m 1 . Fill the gravity cup with water and weigh it to get the mass m of water in the gravity cup. 2 , put the sample wrapped in paraffin into a density cup filled with water, wait for the water in the density cup to overflow, and then weigh the total weight to get m 3 The dry density of the sample is calculated as follows:
[0074]
[0075] Where: ρ—dry density of the sample (g / cm 3 );
[0076] ρ 0 —Density of water (g / cm 3 );
[0077] ρ 1 —Density of paraffin wax (g / cm 3 );
[0078] m 0 —Mass of the sample after drying (g);
[0079] m 1 —Mass of paraffin-wrapped sample (g);
[0080] m 2 —The mass of the specific gravity cup filled with water (g);
[0081] m 3 —Total mass (g) of the sample after adding paraffin wax to wrap it.
[0082] 2. Carbon fixation test
[0083] The unburned brick sample was ground with a mortar, and the ground sample was passed through a 0.45 mm square hole sieve to obtain a powder sample. The powder sample was placed in a crucible, and the crucible was placed in a muffle furnace and heated to 840 °C. 2 The absorption rate is calculated as follows:
[0084]
[0085] Where: W t —CO 2 Absorption rate (%);
[0086] ΔW 540-840 ℃—The mass lost when the sample is heated from 540℃ to 800℃ (g):
[0087] ΔW 105 ℃—The mass of the sample when heated to 105℃ (g).
[0088] The dry density of the bricks was measured to be 1.21 g / cm 3 , the carbon fixation rate is 5.3%.
[0089] Example 2
[0090] The basic implementation of this embodiment is the same as that of Embodiment 1, except that the carbon dioxide foaming solution added in this embodiment is obtained by mixing sodium dodecylbenzene sulfonate (SDBS) with a concentration of 4.5 g / L and hydroxypropyl methylcellulose with a concentration of 2 g / L.
[0091] The performance of the unburned bricks obtained in this example was tested. Referring to the standard "Standard for Geotechnical Test Methods" (GB / T50123-2019) and the brick dry density and carbon fixation rate determination method proposed in Example 1, it was determined that the compressive strength of the unburned bricks was 9.7 MPa and the dry density of the bricks was 1.26 g / cm 3 , water absorption rate is 15%, softening coefficient is 0.8, and carbon fixation rate is 5.1%.
[0092] Example 3
[0093] The basic implementation of this embodiment is the same as that of Embodiment 1, except that the waste mud used in this embodiment is obtained from a shield tunneling project and has a water content of 110%.
[0094] The performance of the unburned bricks obtained in this example was tested. Referring to the standard "Standard for Geotechnical Test Methods" (GB / T50123-2019) and the brick dry density and carbon fixation rate determination method proposed in Example 1, it was determined that the compressive strength of the unburned bricks was 9.9 MPa and the dry density of the bricks was 1.19 g / cm 3 , water absorption rate is 16%, softening coefficient is 0.8, and carbon fixation rate is 5.2%.
[0095] Example 4
[0096] The basic implementation method of this embodiment is the same as that of Example 1, except that the waste mud used in this embodiment is obtained from a shield project and has a water content of 110%; the added carbon dioxide foaming solution is obtained by mixing fatty alcohol polyoxyethylene ether sodium sulfate (AES) with a concentration of 4.5 g / L and hydroxypropyl methylcellulose with a concentration of 2 g / L.
[0097] The performance of the unburned bricks obtained in this example was tested. Referring to the standard "Standard for Geotechnical Test Methods" (GB / T50123-2019) and the brick dry density and carbon fixation rate determination method proposed in Example 1, it was determined that the compressive strength of the unburned bricks was 9.6 MPa and the dry density of the bricks was 1.23 g / cm 3 , water absorption rate is 16%, softening coefficient is 0.8, and carbon fixation rate is 4.9%.
[0098] Example 5
[0099] The basic implementation of this embodiment is the same as that of Embodiment 1, except that the water content of the waste slurry used in this embodiment is 120%.
[0100] The performance of the unburned bricks obtained in this example was tested. Referring to the standard "Standard for Geotechnical Test Methods" (GB / T50123-2019) and the brick dry density and carbon fixation rate determination method proposed in Example 1, it was determined that the compressive strength of the unburned bricks was 8.6 MPa and the dry density of the bricks was 1.10 g / cm 3 , water absorption rate is 18%, softening coefficient is 0.8, and carbon fixation rate is 4.9%.
[0101] Example 6
[0102] The basic implementation of this embodiment is the same as that of Example 1, except that the waste mud used in this embodiment has a water content of 120%; the added carbon dioxide foaming solution is obtained by mixing sodium dodecylbenzene sulfonate (SDBS) with a concentration of 4.5 g / L and hydroxypropyl methylcellulose with a concentration of 2 g / L.
[0103] The performance of the unburned bricks obtained in this example was tested. Referring to the standard "Standard for Geotechnical Test Methods" (GB / T50123-2019) and the brick dry density and carbon fixation rate determination method proposed in Example 1, it was determined that the compressive strength of the unburned bricks was 7.9 MPa and the dry density of the bricks was 1.20 g / cm 3 , water absorption rate is 19%, softening coefficient is 0.75, and carbon fixation rate is 4.5%.
[0104] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0105] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A light-weight, unburned brick made of all-solid waste based on carbon dioxide foaming technology, characterized in that: It comprises the following components in parts by weight: 65-70 parts of waste mud, 14-18 parts of carbon dioxide foam, 3-5 parts of desulfurized gypsum, 3-5 parts of alkali activator, and 5-7 parts of slag.
2. The all-solid waste system lightweight unburned brick based on carbon dioxide foaming technology according to claim 1, characterized in that: The carbon dioxide foam is obtained by whipping a foaming solution at a speed of 600 r / min in a closed carbon dioxide environment.
3. The all-solid waste system lightweight unburned brick based on carbon dioxide foaming technology according to claim 2, characterized in that: The foaming solution is obtained by mixing 4.5 g / L of dodecylamine polyoxyethylene ether and 2 g / L of hydroxypropyl methylcellulose.
4. The all-solid waste system lightweight unburned brick based on carbon dioxide foaming technology according to claim 3, characterized in that: The pore diameter of the carbon dioxide foam is 0.8-1 mm.
5. The all-solid waste system lightweight unburned brick based on carbon dioxide foaming technology according to claim 1, characterized in that: The water content of the waste mud is 100-120%.
6. The all-solid waste system lightweight unburned brick based on carbon dioxide foaming technology according to claim 1, characterized in that: The particle size of the desulfurized gypsum is less than 0.08 mm.
7. The all-solid waste system lightweight unburned brick based on carbon dioxide foaming technology according to claim 1, characterized in that: The alkaline activator is MgO, and the particle size of the alkaline activator is less than 0.08 mm.
8. The all-solid waste system lightweight unburned brick based on carbon dioxide foaming technology according to claim 1, characterized in that: The slag is S95 grade slag powder, and the particle size of the slag is 46-100 μm.
9. A method for preparing lightweight unburned bricks from a full solid waste system based on carbon dioxide foaming technology as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Screening the waste mud to remove debris from the waste mud for later use; (2) drying the desulfurized gypsum, alkali activator and slag respectively, then grinding and sieving to obtain original powder; (3) Weighing the waste mud, desulfurized gypsum, alkali activator and slag in proportion; (4) pouring the components weighed in step (3) into a blender and mixing at a stirring rate of 1000 r / min for 30 min to obtain a mixture I; (5) mixing 4.5 g / L of dodecylamine polyoxyethylene ether and 2 g / L of hydroxypropyl methylcellulose to obtain a foaming solution, whipping the solution at a rate of 600 r / min in a closed carbon dioxide environment to obtain carbon dioxide foam, and taking a proportional amount of the carbon dioxide foam; (6) adding carbon dioxide foam to mixture I and mixing at a stirring rate of 60 r / min for 7 min to obtain mixture II; (7) Place the mixture II in a dry and ventilated place for aging for 6-10 hours, turning it 4-5 times during the aging process; (8) Pour the aged mixture II into the brick mold, smooth the surface, and solidify it after natural drying and proper maintenance; (9) demoulding and sampling, taking out the solidified brick along the direction of the mold groove to obtain the unfired brick sample; (10) The unfired brick sample is placed at 20±2° C. and cured at a humidity of 90% for 28 days to obtain a final product, a lightweight unfired brick.
10. The method for preparing lightweight unburned bricks from a full solid waste system based on carbon dioxide foaming technology according to claim 9, characterized in that: The carbonization reaction process that occurs during the mixing of carbon dioxide foam and mixed slurry is as follows: MgO+H2O→Mg(OH)2 Mg(OH)2+CO2+2H2O→MgCO3·3H2O Mg(OH)2+CO2→Mg5(CO3)4(OH)2·4H2O 5Mg(OH)2+4CO2+H2O→(Mg)5(CO3)4(OH)2·5H2O Ca(OH)2+CO2→CaCO3 3CaO·2SiO2·3H2O+CO2→CaCO3+2CaO·2SiO2·3H2O 3CaO·2SiO2·3H2O+2CO2→2CaCO3+CaO·2SiO2·3H2O 3CaO·2SiO2·3H2O+3CO2→3CaCO3+2SiO2·3H2O.